Determination of Heavy Metal Concentration of Mosses in Degirmendere Valley of Trabzon Province of Turkey - Batan, Nevzat; Ozdemir, Turan; Mendil, Durali (Asian Journal of Chemistry, 2011)
The aim of this study is to determine environmental pollution in degirmendere Valley on the basis of Cu, Cd, Pb, Zn, Mn, Fe, Cr and Ni concentrations in Mosses. The metal ions concentrations were determined in polluted and unpolluted species and soils collected from a wide range of sites with different degrees of metal pollution (Akoluk, Deliklitas, Hacimehmet district) and from control site (Çamburnu-Sürmene). Eight elements were analyzed using atomic absorption spectrometry (AAS). All the elements that measured were found to be at high levels in samples collected from polluted areas including coal mining and crushing and screening plants.